2022
DOI: 10.3389/fmed.2021.758118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to SARS-CoV-2 Following Natural Infection and Vaccination in Irish Hospital Healthcare Workers: Changing Epidemiology as the Pandemic Progresses

Abstract: BackgroundIn October 2020 SARS-CoV-2 seroprevalence among hospital healthcare workers (HCW) of two Irish hospitals was 15 and 4. 1%, respectively. We compare seroprevalence in the same HCW population 6 months later, assess changes in risk factors for seropositivity with progression of the pandemic and serological response to vaccination.MethodsAll staff of both hospitals (N = 9,038) were invited to participate in an online questionnaire and SARS-CoV-2 antibody testing in April 2021. We measured anti-nucleocaps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…We found that HCWs aged ≥35 years had a lower risk of SARS-CoV-2 infection than those aged <35 years, probably due to higher concern regarding possible unfavorable outcomes of infection leading to higher compliance with preventive measures in that age group [ 27 , 28 ]. A similar trend has been reported in some studies [ 10 , 29 , 30 ], whereas other suggest older ages are more likely to be infected [ 11 , 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…We found that HCWs aged ≥35 years had a lower risk of SARS-CoV-2 infection than those aged <35 years, probably due to higher concern regarding possible unfavorable outcomes of infection leading to higher compliance with preventive measures in that age group [ 27 , 28 ]. A similar trend has been reported in some studies [ 10 , 29 , 30 ], whereas other suggest older ages are more likely to be infected [ 11 , 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Male sex has been identified as a risk factor in HCWs for SARS-CoV-2 seropositivity in a number of studies [ 2 , 16 , 17 ] with quoted odds ratios ranging from 1.39 to 3.21. The Prevalence of COVID-19 in Irish Healthcare Workers Study, an independent multicentre seroprevalence study of anti-SARS-CoV-2 antibodies in HCWs in Ireland, which included the current study site, found an increased risk of SARS-CoV-2 seropositivity in male HCWs with an aRR 1.2 (95% CI 1.0–1.4, P = 0.016) [ 13 ]. Studies have demonstrated heterogeneous immune responses to SARS-CoV-2 infection in men and women, including delayed peaks in anti-SARS-CoV-2 immunoglobulins in men [ 18 , 19 ], however these findings generally are inconclusive and lack statistical analysis to relate these findings to infectivity or disease severity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variability in SARS-CoV-2 infection by job role has been demonstrated in a number of studies, with nursing staff and HCAs [ 5 , 6 , 13 , 14 , 30 ] often cited as being at increased risk of infection. In our findings, no individual job role was determined to have consistently increased risk of infection following a given in-work COVID-19 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Using anti-N antibody to identify BTIs, Laing et al reported a BTI rate of 0.88% for symptomatic infection and 25% for asymptomatic infection in 227 healthcare workers ( 21 ). Others reported BTI rates of 0.6 and 0.8% among 4111 and 130 fully vaccinated healthcare workers, respectively ( 35 , 36 ). Another study reported a BTI rate of 4.6 and 5.3% in patients with immune-mediated inflammatory diseases with ( n = 3207) and without immunosuppressants ( n = 985), respectively, and 4.0% in 822 healthy controls ( 37 ).…”
Section: Discussionmentioning
confidence: 99%